ANTIOXIDANT ACTIVITY OF ETHYL ACETATE EXTRACT OF RED Psidium guajavaL. LEAVES GROWN IN MANOKO, LEMBANG - INDONESIA - Fidrianny, Irda; Hartanti, Rika; Raveendaran, Narmmatha (Indonesian Journal of Pharmacy, 2012)
Psidium  guajava L.  (Myrtaceae)  is  a  well  known  plant  in Malaysia  and  Indonesia.  Its  leaves  extract  was  found  to  possess antidiarrhea,  antimicrobial,  hepatoprotective  and  antioxidant activities.  Objective  of  this  research  is  to  isolate  an  antioxidant subtance   from  Red Psidium  guajava L.  leaves.  The  crude  leaves was extracted using Soxhlet apparatus by gradual polarity of three different  solvents,  n-hexane,  ethyl  acetate  and  methanol. Antioxidant  activity  of  each  extract  was  tested  by  using  DPPH (2,2-diphenyl-1-picrylhydrazyl)  radical  scavenging  method.  Total phenol,  total  flavonoid  and  total  tannin  content  of  the  extracts were  also  measured.  Ethyl  acetate extract  was fractionated  using vacuum  liquid  chromato-graphy  for  fractionation.  Purification  was performed using TLC  preparative. Isolate then characterized using specific  spray  reagent,  UV-Vis  spectrophotometry  and  infrared spectrophotometry.  Crude  drug  of  Psidiumguajava contained flavonoid,  tannin,  quinone,  saponin  and  steroid/  triterpenoid. Antioxidant  activity  of  ethyl  acetate  extract  is  65.63%  with  total phenol  4.25%,  total  flavonoid  0.53%  and  total  tannin  1.16%. Antioxidant  compound N was  isolated  from  ethyl  acetate  extract.Antioxidant  compound N was  supposed  to  be   aglycone  flavone that has OH at C -4’, C-5 and C-7.Key words: Psidium guajava L. , antioxidant activity, ethyl acetate extract